Inovasi Jasmeen Florist Bengkulu Dalam Membangun Ketahanan Usaha Di Era Digital” - Indriana Indriana; Silke Sachanovrissa; Dodi Hardinata (Utami Publisher, 2026)
This study analyzes the innovation strategies of Jasmeen Florist Bengkulu in building business resilience in the digital era. Using a descriptive qualitative approach through interviews, observations, and documentation, the study found that Jasmeen Florist successfully combined creativity, digital marketing, and community collaboration to enhance competitiveness and strengthen economic, social, and psychological resilience. The use of social media, online ordering systems, and creative visual content emerged as key success factors, supported by product diversification, local workforce empowerment, and adaptation to digital trends. These findings enrich the literature on digital entrepreneurship in the local florist sector and provide valuable insights for MSME practitioners, academics, and local governments in fostering an adaptive and sustainable creative business ecosystem.